2020
DOI: 10.1038/s41598-020-74689-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection of EGFR mutations by cell-free loop-mediated isothermal amplification (CF-LAMP)

Abstract: Targeting epidermal growth factor receptor (EGFR) through tyrosine kinase inhibitors (TKI) is a successful therapeutic strategy in non-small cell lung cancer. However, the response to TKI therapy depends on specific activating and acquired mutations in the tyrosine kinase domain of the EGFR gene. Therefore, confirming the EGFR status of patients is crucial, not only for determining the eligibility, but also for monitoring the emergence of mutations in patients under TKI therapy. In this study, our aim was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…A second report from the same research group demonstrated a cost effective and sensitive LAMP for detecting therapeutically-relevant EGFR hotspot mutations in a non-invasive manner. The results consistency when compared to those obtained by ultrasensitive droplet digital PCR (ddPCR) assay indicates the robustness of the developed method 33 .…”
Section: Discussionsupporting
confidence: 53%
“…A second report from the same research group demonstrated a cost effective and sensitive LAMP for detecting therapeutically-relevant EGFR hotspot mutations in a non-invasive manner. The results consistency when compared to those obtained by ultrasensitive droplet digital PCR (ddPCR) assay indicates the robustness of the developed method 33 .…”
Section: Discussionsupporting
confidence: 53%
“…Here we demonstrate a compact AS-Mini-LAMP + USS mutant speci c reaction that consists of 6-primers (FIP, BIP, F3, B3, USS FB, USS BB) spanning 155 bp, within the typical range of plasma cfDNA. In contrast to alternative mutation-selective LAMP design strategies (PNA-LNA-LAMP 11 and AS-LAMP/CF-LAMP 13,14 ) selectivity is encoded at the terminal 5' position of both the FIP and BIP primers, promoting selective self-primed exponential ampli cation upon self-hybridisation and loop formation from the FIP and BIP initiated reactions. Using synthetic template models, the mutant selective reaction (AS-Mini-LAMP Mut + USS WT ) demonstrated analytical sensitivity of 500 copies of mutant DNA within 25 minutes, > 20 minutes ahead of non-selective WT template.…”
Section: Discussionmentioning
confidence: 99%
“…Arjuna et al, 13 developed allele-speci c LAMP (AS-LAMP), a typical 6-primer LAMP reaction, incorporating the T790M EGFR mutation or wild type counterpart in the backward inner primer (BIP). Subsequent application on cfDNA template material (termed CF-LAMP) included a pre-LAMP conventional PCR using LAMP outer primers (F3 and B3) to enrich for copies of target cfDNA prior to CF-LAMP 14 . Our previous work describes a universal self-stabilising single base-LAMP method (USS-sbLAMP) 5 , a typical 6-primer reaction encoding single base variant selectivity at the 5' end of both the forward and backward inner primers (FIP and BIP), coupled with unmodi ed self-stabilising (USS) competitive primers for enhanced prevention of un-speci c wild type variant base ampli cation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no reports of such variations being detected in plasma by droplet digital PCR (ddPCR) technique, the most advanced third generation ultrasensitive PCR technique. We have previously reported that ddPCR can efficiently detect EGFR variations in lung cancer patient-derived plasma [11,12]. Here we are reporting a series of 6 cases of de novo SCLC harbouring common as well as rare activating EGFR variations in the plasma as detected by droplet digital PCR (ddPCR).…”
Section: Introductionmentioning
confidence: 99%